Molecular approaches in natural resource conservation and management - DeWoody, J. Andrew 1969- (Cambridge University Press, 2010)
"Intended for undergraduate and graduate students in conservation biology, natural resource management, and ecology, this book compiles compelling case histories in molecular ecology"--Provided by publisher.